Pengaruh Pesan Kampanye #AdaApaDisini terhadap Citra Kemenparekraf : Survei pada Followers Akun Instagram @kemenparekraf.ri - Aqila Shafa; Istisari Bulan Lageni (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
Image is the main goal as well as the achievement to be achieved in the world of public relations. Therefore, Kemenparekraf created the #AdaApaDiSini campaign using Instagram social media. The #AdaApaDiSini campaign contains messages about places, nature, and culture in an Indonesian tourism area to be seen by the public. The purpose of this study is to determine the #AdaApaDiSini campaign message on Instagram @Kemenparekraf.ri, the image of Kemenparekraf regarding the #AdaApaDiSini campaign message and to determine whether or not there is an influence of the #AdaApaDiSini campaign message on the image of Kemenparekraf itself. The theory used in this research is the campaign message theory which has the dimensions of message structure, message content, framing, language, and emotional appeal (Perloff, 2017). This research also uses image theory which has dimensions of perception, cognition, motives, and attitudes (Soemirat & Ardianto, 2017). The method used in this research is a quantitative approach with a survey method and simple random sampling technique by distributing questionnaires in the form of google forms to 98 respondents selected according to the characteristics of the study. From the results of calculations and data using the SPSS 25 application, the #AdaApaDiSini campaign message affects the image of Kemenparekraf by 34.7%.